Arm position during daily activity - Coley, Brian; Jolles, Brigitte M.; Farron, Alain; Aminian, Kamiar (Gait & posture, 2008)
A new method of evaluation for functional assessment of the shoulder during daily activity is presented. An ambulatory system using inertial sensors attached on the humerus was used to detect the ability to work at a specific position of the shoulder. Nine arm positions were defined based on humerus elevation. The method was tested on 31 healthy volunteer subjects. First, we estimated the ability of the system to detect the different elevation angles and arm positions of each subject. Following that, we evaluated their arm positions during approximately 8 h of daily activities. Each arm position was recognized with a good sensitivity (range 80–100%) and specificity (range 96–99%). During daily activity, we estimated the frequency (number/h) that the humerus reached each arm position during the periods of 0–1 s (period P1), 1–5 s (period P2) and 5–30 s (period P3). Our data showed that all subjects had 96% of their arm position reached under the 5th level (100–120°). No significant difference was observed between dominant and non-dominant sides for the frequency and duration of arm positions ( p > 0.3). Our evaluation was in accordance with the clinical questionnaire (the Constant score) for the P1 duration, but differed for longer periods P2 and P3. By quantifying the arm positions and their durations for both shoulders, we proposed a new score to evaluate the ability to work at a specific level based on the symmetry index of the arms activity. Using this score, we obtained, on average, good symmetry for healthy subjects. This score can be useful in evaluating the asymmetry in arm function in patients with a shoulder disease. The proposed technique could be used in a number of shoulder diseases where problems in performing daily activities should be expressed in terms of objective measure of arm position.